Pseudomonas aeruginosa Enolase Influences Bacterial Tolerance to Oxidative Stresses and Virulence - Weng, Yuding; Chen, Fei; Liu, Yiwei; Zhao, Qiang; Chen, Ronghao; Pan, Xiaolei; Liu, Chang; Cheng, Zhihui; Jin, Shouguang; Jin, Yongxin; Wu, Weihui (Frontiers in Microbiology, 2016)
Pseudomonas aeruginosa is a Gram negative opportunistic pathogenic bacterium, which causes acute and chronic infections. Upon entering host, bacteria alter global gene expression to adapt to host environment and avoid clearance by host. Enolase is a glycolytic enzyme involved in carbon metabolism. It is also a component of RNA degradosome, which is involved in RNA processing and gene regulation. Here we report that enolase is required for the pathogenesis of P. aeruginosa in a murine acute pneumonia model. Mutation of enolase coding gene (eno) increased bacterial susceptibility to neutrophil mediated killing, which is due to reduced tolerance to oxidative stress. Catalases and alkyl hydroperoxide reductases play a major role in protecting the cell from oxidative damages. In the eno mutant, the expression levels of catalases (KatA, KatB) were similar as those in the wild type strain in the presence of H2O2, however, the expression levels of alkyl hydroperoxide reductases (AhpB, AhpC) were significantly reduced. Overexpression of ahpB but not ahpC in the eno mutant fully restored the bacterial resistance to H2O2 as well as neutrophil mediated killing, and partially restored bacterial virulence in the murine acute pneumonia model. Therefore, we have identified a novel role of enolase in the virulence of P. aeruginosa.